Activation of preformed EGF receptor dimers by ligand-induced rotation of the transmembrane domain - Morikia, T.; Maruyama, H.; Maruyama, I.N.
The epidermal growth factor receptor plays crucial roles throughout the development of multicellular organisms, and inappropriate activation of the receptor is associated with neoplastic transformation of many cell types. The receptor is thought to be activated by ligand-induced homodimerisation. Here, however, we show by chemical cross-linking and sucrose density-gradient centrifugation that in the absence of bound ligand the receptor has an ability to form a dimer and exists as a preformed dimer on the cell surface. We also analysed the receptor dimerisation by inserting cysteine residues at strategic positions about the putative -helix axis of the extracellular juxtamembrane region. The mutant receptors spontaneously formed disulphide bridges and transformed NIH3T3 cells in the absence of ligand, depending upon the positions of the cysteine residue inserted. Kinetic analyses of the disulphide bonding indicate that EGF binding induces flexible rotation or twist of the juxtamembrane region of the receptor in the plane parallel with the lipid bilayer. The binding of an ATP competitor to the intracellular domain also induced similar flexible rotation of the juxtamembrane region. All the disulphide-bonded dimers had flexible ligand-binding domains with the same biphasic affinities for EGF as the wild-type. These results demonstrate that ligand binding to the flexible extracellular domains of the receptor dimer induce rotation or twist of the juxtamembrane regions, hence the transmembrane domains, and dissociate the dimeric, inactive form of the intracellular domains. The flexible rotation of the intracellular domains may be necessary for the intrinsic catalytic kinase to become accessible to the multiple tyrosine residues present in the regulatory domain and various substrates, and may be a common property of many cell-surface receptors, such as the insulin receptor.
Keywords: CELL-SURFACE RECEPTOR; TRANSMEMBRANE SIGNALLING; CYSTEINE DISULPHIDE CROSS-LINKING; MOLECULAR MECHANISM; MODEL